Analisis Evaluatif Berbasis Dokumen Gerakan Tujuh Kebiasaan Anak Indonesia Hebat Jenjang SMP Dengan Model CIPP - I Nyoman Haryantara; Fifi Lesley Florence Pogoh; Mohammad Munir; I Wayan Sukra Warpala; I Kadek Suartama (Cetta: Jurnal Ilmu Pendidikan, 2026)
The Seven Habits of Great Indonesian Children Movement (Gerakan Tujuh Kebiasaan Anak Indonesia Hebat) is a national character-strengthening program based on daily habituation at the junior high school (Sekolah Menengah Pertama/SMP) level. This study aims to analyze the program's design logic and implementation readiness using the Context, Input, Process, and Product (CIPP) model. This qualitative documentary evaluation study analyzed secondary data consisting of 3 official ministry guideline documents (published in 2025) and 15 empirical literature articles (2020–2025) selected based on relevance criteria regarding character education, child health, and program evaluation. Data were analyzed using content analysis by matching document substances against the eligibility criteria of each CIPP component. The evaluation results at the document level indicate: (1) Context: the program design demonstrates high relevance in addressing character decline, health issues, and digital distractions among SMP students; (2) Input: policy documents adequately include guides for teachers and parents, yet lack operational monitoring instrument criteria; (3) Process: the planned implementation mechanism is theoretically sound, but risks becoming ceremonial without integration into school culture; and (4) Product: success criteria in the design documents are feasible to be developed into longitudinal behavioral indicators. The study concludes that the program design is conceptually viable and ready for implementation at the SMP level, provided that its sustainability relies on measurable operational monitoring tools.